Editorial: Three Tenets of Environmental Importance - Wilkinson, Nicholas (Emerald Group Holdings Ltd., 2015)
These are Working, Learning and Living. The first and last of Working and Living have been addressed in some of the previous issues of the journal. ‘Working’ has been supported and developed by books, journals and projects. User decision making processes lie central to these concepts. © 2015 Emerald Publishing Limited.